BEST PRACTICE OF STUDY THE TERMINOLOGY OF ECOLOGY ON THE BASIS OF UZBEK AND ENGLISH LANGUAGES - Nigmatullina Almira Shamsunovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
For a start, environmental problems, issues of their study and solutions are among the most important and priority areas of modern science. Ecology in the era of the rapid development of the latest technologies has a strong influence on all spheres of human life, both on its material and spiritual culture. With the development of environmental science, new concepts and realities appear that need appropriate nominations. Therefore, a comprehensive study of the vocabulary and terms of ecology and their scientifically based interpretation remain relevant and significant.